The Influence of Unconscious Perceptual Processing on Decision-Making: A New Perspective From Cognitive Neuroscience Applied to Generation Z - Sutil-Martín, Dolores Lucía; Rienda-Gómez, Juan José (Frontiers in Psychology, 2020)
Cognitive neuroscience and technological development applied in it have revolutionized the world of marketing by responding to problems that marketing itself had not been able to solve. Questions such as what area of the brain should be stimulated to make the consumer's purchase decision real and not a simple intention, how information is processed when making a decision, what personality characteristics affect the decision to shopping, etc., must respond to new marketing challenges. Issues like these have opened the door to the consumer's brain. Using subliminal messages has been on minds of scientists, generating much controversy. Many have shown that making sound decisions based on intuition rather than conscious reasoning, is more common than previously thought. In fact, they have shown that sound intuitive decision making basically depends on the association of the subliminal messages of a given situation with the limbic brain structures formed. They have concluded the brain does not consciously need to know contextual information to learn the value of this information and make the necessary linkages to make productive decisions. In this study we consider whether unconscious perceptual processing influences decision-making, and explore the influence of aspects of personality that are related to unconscious processing, such as the degree of neuroticism, extroversion and gender of the individual, applied to Z generation, besides whether the stimuli are either verbal or pictorial, Backward visual masking paradigm has been used to assure the unconscious perceptual processing. To test these assumptions, a set of ANOVA models and logistic regressions were carried out where the dependent variable is whether the people perceived the stimuli or not, and the independent variables were gender, pictorial or verbal stimuli and personality facts, such as extroversion, introversion and neuroticism. The results suggest verbal stimuli work better than pictorial stimuli, maybe because pictures need to be improved or they are not working well. However, considering those verbal stimuli, the gender and level of neuroticism are important variables to influence in the unconscious perceptual decision making processes. In fact, be a women having a high level of neuroticism means to be more permeable to unconscious perceptual processes.